2012
DOI: 10.1021/ja3050579
|View full text |Cite
|
Sign up to set email alerts
|

Stable Tetrabenzo-Chichibabin’s Hydrocarbons: Tunable Ground State and Unusual Transition between Their Closed-Shell and Open-Shell Resonance Forms

Abstract: Stable open-shell polycyclic aromatic hydrocarbons (PAHs) are of fundamental interest due to their unique electronic, optical, and magnetic properties and promising applications in materials sciences. Chichibabin's hydrocarbon as a classical open-shell PAH has been investigated for a long time. However, most of the studies are complicated by their inherent high reactivity. In this work, two new stable benzannulated Chichibabin's hydrocarbons 1-CS and 2-OS were prepared, and their electronic structure and geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(183 citation statements)
references
References 93 publications
10
171
0
2
Order By: Relevance
“…Wu et al reported derivatives of Chichibabin's hydrocarbon, 133-CS/133-OS and 134-CS/134-OS ( Figure 17) [155]. The time-dependent UV-vis-NIR absorption spectra of the 133-OS biradical showed that the absorption spectrum of the biradical diminished with time and the final spectrum after the decay entirely matched with the stable quinoidal form 133-CS (Figure 18a).…”
Section: Polycyclic Aromatic Hydrocarbon Radicalsmentioning
confidence: 97%
“…Wu et al reported derivatives of Chichibabin's hydrocarbon, 133-CS/133-OS and 134-CS/134-OS ( Figure 17) [155]. The time-dependent UV-vis-NIR absorption spectra of the 133-OS biradical showed that the absorption spectrum of the biradical diminished with time and the final spectrum after the decay entirely matched with the stable quinoidal form 133-CS (Figure 18a).…”
Section: Polycyclic Aromatic Hydrocarbon Radicalsmentioning
confidence: 97%
“…Recently two types of tetrabenzo derivatives 15 and 16 of 2 were isolated by Wu and their biradicaloid behaviors were thoroughly investigated by means of X-ray crystallographic and spectroscopic measurements. 38 The interesting point of the benzannulated compounds lies in that the electronic structure of the ground state is determined by the energy balance between structural strain and π-bond formation. Due to the steric hindrance around the anthracene moiety, 15 and 16 adapt not a planar form but an orthogonal or folded form as the most stable form.…”
Section: 32mentioning
confidence: 99%
“…[4e, 8] Over the last few years,v arious derivatives and analogues of TH and CH with enhanced stability and diradical character have been prepared using kinetic and/or thermodynamic stabilization approaches. [9a,10] Spin delocalization with extended p-conjugated systems using a" benzannulation" approach [11] has also been used to stabilize carbon-centered diradicals such as III.Nevertheless, the number of carbon-centered diradicals remains limited. [9a,10] Spin delocalization with extended p-conjugated systems using a" benzannulation" approach [11] has also been used to stabilize carbon-centered diradicals such as III.Nevertheless, the number of carbon-centered diradicals remains limited.…”
mentioning
confidence: 99%